Effect of different insecticides and dosages on the germination of corn seed - Oliveira, Lenita J.; Cruz, Ivan (Pesquisa Agropecuaria Brasileira, 2014)
Three laboratory experiments were conducted at Sete Lagoas, MG, Brazil, to verify the effect of four insecticides (acephate, aldrin, carbofuran and thiodicarb) at different dosages on germination of com seed (Zea mays L.), under various storage periods. The seeds were treated and stored under absence or presence of light. Laboratory routine germination tests started at the same day of seed treatment and continued thereafter each ten days up to 30 days in the first experiment, and in each 28 days up to 16 weeks, in the second and third experiments. The evaluation was performed seven days after the starting date of each germination test, based on the number of normal and abnormal seedlings and dead seeds. All insecticides showed some adverse effect on germination. However, only carbofuran affected adversely seed germination when older seeds were put to germinate on the same day of insecticide treatment. At this time, the germination for carbofuran plots was 12.8% less than for the untreated ones. The effect of light was different for the several insecticides, being adverse mainly for thiodicarb.